Competition and banks' financial performance in dual banking: Evidence from efficiency-adjusted market power - Mudeer Ahmed Khattak; Mohsin Ali; Noureen A. Khan (Economic Journal of Emerging Markets, 2022)
Purpose ― This paper examines banking competition's effect on Malaysia's financial performance from 2008–2020. This study investigates the relationship between banks' market competition and financial performance by examining banks' profits and risks. Further, this current study examines whether the association differs for Islamic banks. Methods ― The research studies Malaysia as a sample country and employs a data span from 2008-2020. In order to address omitted variable bias, simultaneity and endogeneity are avoided using a two-step GMM model. Findings ― Our results recommend that more competition inspires the banking sector to invest in risky ventures to offset the losses in revenues. Moreover, banking today is still based on basic banking operations like granting loans (or financing in Islamic banks), collecting deposits, and managing payment systems. Implication ― Since our findings show a negative effect of competition on the bank's financial performance, we suggest that competition lowers banks' profits and results in greater risk. It is suggested that regulators and policymakers develop the financial infrastructure in terms of controlled competition in banking and encourage banks to diversify their operations efficiently. We find no significant difference in the association between conventional and Islamic banking. Originality ― This research is the first to examine the effect of bank competition on the financial performance of a developed dual banking system using the efficiency-adjusted Lerner index.